2003
DOI: 10.1037/0735-7044.117.2.341
|View full text |Cite
|
Sign up to set email alerts
|

Effects of D-cycloserine on extinction of conditioned freezing.

Abstract: The present study tested the prediction that D-cycloserine (DCS), a partial N-methyl-D-aspartate agonist, would facilitate extinction of conditioned freezing in male Sprague-Dawley rats. Rats received 5 light-shock pairings (conditioning). The following day, rats received 6 light-alone presentations (extinction training). Twenty-four hours later, rats received 1 light-alone presentation (test). Subcutaneous DCS injection before or after extinction training significantly enhanced extinction, and the dose-respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

31
315
3
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 369 publications
(350 citation statements)
references
References 35 publications
31
315
3
1
Order By: Relevance
“…Recent studies indicate that glutamate NMDA receptors in the amygdala play a critical role in the extinction of conditioned fear (Walker et al, 2002;Ledgerwood et al, 2003Ledgerwood et al, , 2004Yang and Lu, 2005). This experiment assessed the role of amygdaloid NMDA receptors in the DEX effect, two glutamate NMDA receptor antagonists (7)-HA966 and MK801 were used.…”
Section: Experiments Three: Dex Facilitation Effect On Extinction Was mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies indicate that glutamate NMDA receptors in the amygdala play a critical role in the extinction of conditioned fear (Walker et al, 2002;Ledgerwood et al, 2003Ledgerwood et al, , 2004Yang and Lu, 2005). This experiment assessed the role of amygdaloid NMDA receptors in the DEX effect, two glutamate NMDA receptor antagonists (7)-HA966 and MK801 were used.…”
Section: Experiments Three: Dex Facilitation Effect On Extinction Was mentioning
confidence: 99%
“…These results suggest that brain glucocorticoids may be involved in the dysregulation of fear memory extinction in PTSD patients. Evidence also indicated that administration of the partial NMDA receptor agonist D-cycloserine (DCS) facilitated extinction of conditioned fear (Walker et al, 2002;Ledgerwood et al, 2003Ledgerwood et al, , 2004Ressler et al, 2004;Yang and Lu, 2005) and numerous signaling cascades are involved in the DCS effect on extinction that include mitogen-activated protein kinase (MAPK), phosphatidylinositol 3-kinase (PI-3 kinase) and calcineurin (Yang and Lu, 2005). The amygdaloid NMDA receptors may be also involved in the facilitatory effect of glucocorticoids on the extinction.…”
Section: Introductionmentioning
confidence: 99%
“…Converging evidence from a variety of studies indicates that the process of extinction can be enhanced with pharmacological intervention (Walker et al, 2002;Ledgerwood et al, 2003Ledgerwood et al, , 2004Yang et al, 2005b). Ours is the first study we know of showing that acute systemic administration of EGb761 facilitated extinction of conditioned fear.…”
Section: Discussionmentioning
confidence: 83%
“…Recently, glutamate NMDA receptor agonist DCS and glucocorticoid receptor agonist dexamethasone are documented to facilitate extinction of conditioned fear (Walker et al, 2002;Yang et al, 2005b). Either before or after extinction training, systemic injections of DCS (Ledgerwood et al, 2003; or dexamethasone (Yang et al, 2005b) facilitated extinction of conditioned fear. When EGb761 was administered immediately after extinction training, it did not show any facilitation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation